Dugaan Perundungan di Lingkungan Kampus: Studi Kasus Kematian Timothy Anugerah di Universitas Udayana - Sijabat, Margaretha Happy Dianezra (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The death of Timothy Anugerah, a student of Udayana University, has attracted widespread attention from the public, the media, and the academic community. This study aims to analyze the incident from social, ethical, legal, and human rights perspectives, while highlighting the role of higher education institutions and society in preventing similar cases. In Timothy’s case, no strong evidence of bullying during his lifetime was found. However, a phenomenon of posthumous bullying emerged, causing additional psychological distress to the victim’s family. This study also emphasizes the importance of empathy, social ethics, and the protection of students’ human rights, including the right to live safely, peacefully, and free from intimidation. Furthermore, this case underscores the responsibility of universities to provide an academic environment that supports mental well-being, transparency, and psychological support systems. The social and legal reflections drawn from this case serve as a reminder to the entire academic community and society at large that respect for others, the protection of human rights, and character education are essential foundations for creating a safe and humane learning environment.